The role of the chief process officer in organizations. Issue 4 (10th July 2018) - Kratzer, Simon; Lohmann, Patrick; Roeglinger, Maximilian; Rupprecht, Lea; zur Muehlen, Michael
Abstract : Purpose: The design and execution of business processes are important drivers of organizational performance. Organizations design their operations around cross-functional processes adopting business process management (BPM) methods, tools and systems. This often involves assigning BPM accountability to senior executives such as the chief operating officer (COO), chief information officer (CIO), or chief technology officer (CTO). Some organizations appoint a chief process officer (CPO), a phenomenon raising important questions about the skills and responsibilities of this position within the top management team. The purpose of this paper is to conduct an empirical study to explore the skills and responsibilities of CPOs and differences to other executives. Design/methodology/approach: The authors conducted an exploratory content analysis of job resumes from LinkedIn.com to investigate the skills and careers of individuals appointed as COO, CIO, CTO and CPO in organizations from different industries and sizes. The content analysis was complemented with expert interviews of CPOs to obtain rich insights into their perception of the responsibilities of this position. Findings: CPOs possess a unique skill set to serve as change agents. Their skills enable them to serve as integrators and influencers across managerial ranks and corporate functions. COOs, CIOs and CTOs possess more specialized skills related to their corporate function, whereas CPOs are more generalists who facilitate process-oriented strategy and execution, driving cultural change throughout the organization. These findings are consistent across industry and size. Originality/value: This is the first paper to examine the CPO position in relation to other senior executive positions. Hence, it addresses an important gap in the BPM literature which can help organizations to make informed decisions whether they need a CPO position or have it become a part-time role of one of their existing C-level positions.